The girls : Jewish women of Brownsville, Brooklyn, 1940-1995 - Ford, Carole Bell, 1934- (SUNY series in modern Jewish literature and culture., 2000)
"This book tells the stories of the Jewish women who came of age in Brownsville, Brooklyn, in the 1940s and 1950s. Through in-depth interviews with more than forty women, Carole Bell Ford explores the choices these women made and the boundaries within which they made them, offering fresh insights into the culture and values of Jewish women in the postwar period. Not content to remain in the past, The Girls is also a story of women who live in the present, who lead fulfilling lives even as they struggle to adjust to changes in American society that conflict with their own values and that have profoundly affected the lives of their children and grandchildren."--Jacket